2010
DOI: 10.1007/s11846-010-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tax uncertainty on irreversible investment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
0
12
0
5
Order By: Relevance
“…Iz tog razloga, analitičari fenomen poreske neodređenosti analiziraju segmentirano, a najčešće u svjetlu implikacija na investicije. Niemann (2011) je poresku neodređenost defi nirao kao "odstupanje stvarne uplate poreza koja se odnosi na određeni investicioni projekt u odnosu na uplatu poreza koja se očekivala prije donošenja odluke o investiciji".…”
Section: Načelo Određenosti U Finansijskoj Teorijiunclassified
“…Iz tog razloga, analitičari fenomen poreske neodređenosti analiziraju segmentirano, a najčešće u svjetlu implikacija na investicije. Niemann (2011) je poresku neodređenost defi nirao kao "odstupanje stvarne uplate poreza koja se odnosi na određeni investicioni projekt u odnosu na uplatu poreza koja se očekivala prije donošenja odluke o investiciji".…”
Section: Načelo Određenosti U Finansijskoj Teorijiunclassified
“…Pozitivní vliv daňové jistoty na růst potvrzují El-Shazly (2009) nebo Edmiston (2001). Niemann (2004Niemann ( , 2011 naopak pozitivní vliv daňové jistoty na růst, resp. investice, vyvrací, přičemž tvrdí, že vliv není jednoznačný, neboť závisí na celé řadě dalších faktorů, jako vztah k riziku, vývoj úrokových sazeb, rychlost návratnosti investic apod.…”
Section: Vliv Daňové Jistoty Na Ekonomický Růstunclassified
“…Niemann (2004) defined two neutrality conditions: first‐order neutrality, which requires the complete ineffectiveness of taxation on investment decisions; second‐order neutrality, which means that the stochastic nature of taxation does not alter investment decisions. In a subsequent article (Niemann, 2006), he analyzed combined tax‐rate and tax‐base uncertainty by assuming a stochastic tax payment. He showed that the uncertainty of tax payments has an ambiguous impact on investment timing 7 .…”
Section: Introductionmentioning
confidence: 99%